Health innovation project: A concept paper on a virtual health promotion program for men - Tong, S.F.; Khoo, E.M.; Low, W.Y.; Ng, C.J.; Wong, C.H.; Yusoff, H.M.; Abu Bakar, A.I.; Tan, H.M.; Jiwa, M. (2014)
Many causes of mortality and morbidities in men are preventable. Men's poor engagement in health-promoting activities has been attributed to the socially constructed male gender identity. Hence, health innovations to promote men's health have to take into the account their social identity and health-seeking behavior. The innovation should be flexible, interactive, discreet, informative, and user-friendly. It should also facilitate self-care. Innovations that deploy information and computer technology (ICT) are promising. MyMan, a future web and mobile application that incorporates self-assessment, individual risk calculation, projection of future health status, and tailored advice, is in the process of prototype development for testing in the community. The main concern about this application is that it may have limited usefulness to an ICT-naive population. However, this may be overcome by having a similar application in health clinics where assistance in using the technology can be provided. A randomized controlled trial will be conducted to examine the effectiveness of this innovation, which takes into account men's needs for convenience and privacy. Given the widespread use and flexibility of ICT, it has great potential and deserves further evaluation.